Passive Vibration Control by Frictional Energy Dissipation in Refrigerant‐Lubricated Gas Foil Bearing Rotor Systems. Issue 1 (17th December 2018) - Leister, Tim; Seemann, Wolfgang; Bou‐Saïd, Benyebka
Abstract: Even though the dynamic performance of rotors supported by refrigerant‐lubricated gas foil bearings (GFBs) is very sensitive to the amount of energy dissipated in the foil structure, almost none of the existing computational models really capture dry friction with typical stick–slip transitions. The presented work addresses this shortcoming by incorporating an elasto‐plastic bristle friction law into the structural model, which is coupled in an interconnected solution approach to a Reynolds equation for non‐ideal compressible gases and to a modified Jeffcott–Laval rotor model. Numerical results confirm that properly designed GFBs have the potential to benefit significantly from the foil structure acting as a passive vibration control device.